Effects of threonine supplementation on productive performance, carcass and organ weights of fattening guinea pigs with mixed feeding - Paredes, Manuel (2021)
The experiment aimed to evaluate the effects of five dietary levels of threonine (Thr) on growth performance, carcass characteristics, and gastrointestinal (GIT) and visceral tract development of fattening guinea pigs. In total, 40 improved 30-day-old male guinea pigs were randomly distributed in five treatments with four repetitions in a completely random design and slaughtered at 72 days of age. The diet consisted of restricted concentrated feed and green forage ad libitum. Thr supplementation was performed with L-Treonine 98.5% (L-Thr) at levels of 0, 2, 4, 6 and 8 g/kg of feed, to obtain levels of 0.55, 0.59, 0.63, 0.67 and 0.71% of Thr. Guinea pigs with 0.63% dietary Thr achieved greater weight gains, better feed conversion and higher carcass performance. The GIT with possible immunological functions reached a higher relative weight with levels of 0.67 and 0.71% of Thr. The relative weight of the spleen and heart were not affected by Thr levels, while significant differences were observed in liver, lungs and kidneys.